Further studies on the pharmacokinetics of perhexiline maleate in humans - Amoah, A.G.; Gould, B.J.; Parke, D.V.; Lockhart, J.D.F. (Xenobiotica, 1986)
1. We have performed single-dose pharmacokinetic studies on perhexiline in eight young volunteers, each given 300 mg of Pexid orally, using an h.p.l.c. method for the separation and quantification of the drug and its monohydroxy metabolites in plasma and urine. 2. The plasma concentration of the cis-monohydroxyperhexiline (peak of 473 ± 43 ng/ml at 7.5 ± 2.0 h) was always higher than for unchanged perhexiline (peak of 112 ± 20 ng/ml at 6.5 ± 2.0 h) whereas the concentration of the transmetabolite was either low or undetectable in plasma. These findings indicate the occurrence of stereospecific pre-systemic metabolism of perhexiline which reduces the bioavailability of the parent drug. The plasma elimination half-life of perhexiline was 12.4 ± 6.1 h (range 7-23 h) while that for cis-monohydroxyperhexiline was 19.9 ± 7.7 h (range 10-29 h). 3. Not more than 0.3% of unchanged perhexiline was excreted in the urine over five days in eight subjects. Between 3 and 23% of the orally administered drug was excreted as the cis- or trans-monohydroxy metabolites, the ratio of trans to cis metabolites being 0.52 ± 0.20.
Keywords: Adult; Female; Half-Life; Human; Kinetics; Male; Perhexiline